Eficiencia de diferentes fungicidas foliares en época de alta presión para el control de sigatoka negra (Mycosphacerella fijiensis) en banano (Musa paradisiaca) en el campus la María" - Moreno Moreta, Mario Ramon (2020)
In this research, the efficiency of different foliar fungicides in high pressure season was evaluated for the control of black sigatoka (Mycosphaerella fijiensis) in banana (Musa paradisiaca). The development of the experiment was carried out in the experimental plots of the BASF company, located in the "La María" campus belonging to the Quevedo State Technical University. The methodology used for the variables efficacy and efficiency was carried out by visual observation of banana leaves that the statistics of visible stages caused by black sigatoka, with the method proposed by Stover which determines the percentage of infestation, for the analysis of the data was analyzed in a Completely Random Design (DCA), which consists of seven treatments and six repetitions each. The variables were analyzed with the Generalized Linear Model (GLM) with a Quasi-Binominal distribution (P≤0.05). The results that affect the efficacy variable, there is a difference between the evaluated treatments where T5 (Pyraclostrobin) and T6 (Trifloxystrobin) had the ability to fight infection caused by black sigatoka. While the best residuality index for the control of black sigatoka was T5 (Pyraclostrobin) presenting the best results. In conclusion, the T5 treatment (Pyraclostrobin) is effective and cost-effective to combat black sigatoka in banana cultivation. Key words: Banana, control, residuality, black sigatoka.